The art of bonding: informational capital in Dutch green urban citizens' initiatives. (11th December 2017) - van Dam, Rosalie; Salverda, Irini; Hassink, Jan; Vaandrager, Lenneke; Wentink, Carlijn
Abstract: Today's western society is characterized by a transition towards self-organization by citizens in communities. Increasingly, societal problems are addressed by groups of citizens who take action to find concrete solutions. A second feature of western society is that it is an information society in which information and communication play a key role. In this paper, we analyse how these two societal trends come together at the community level. Applying a relational and contingent perspective to how green urban citizens' initiatives develop, we look into the role of information in their interactions with other people, organizations and institutions. We analyse the mechanisms whereby information plays a role in the citizens' initiatives. This leads to the conclusion that informational capital is fundamental to the realization of citizens' initiatives and that informational capital is generated, identified, used and enlarged through the relational strategies of bonding, bridging and linking. It is a process that works in both ways and reinforces citizens' initiatives.